Children and Childhood in Classical Athens - Golden, Mark, 1948- (Book collections on Project MUSE., 2015)
"First published in 1990, Children and Childhood in Classical Athens was the first book in English to explore the lives of children in ancient Athens. Drawing on literary, artistic, and archaeological sources as well as on comparative studies of family history, Mark Golden offers a vivid portrait of the public and private lives of children from about 500 to 300 B.C. Golden discusses how the Athenians viewed children and childhood, describes everyday activities of children at home and in the community, and explores the differences in the social lives of boys and girls. He details the complex bonds among children, parents, siblings, and household slaves, and he shows how a growing child's changing roles often led to conflict between the demands of family and the demands of community. In this thoroughly revised edition, Golden places particular emphasis on the problem of identifying change over time and the relationship of children to adults. He also explores three dominant topics in the recent historiography of childhood: the agency of children, the archaeology of childhood, and representations of children in art. The book includes a completely new final chapter, text and notes rewritten throughout to incorporate evidence and scholarship that has appeared over the past twenty-five years, and an index of ancient sources"--Provided by publisher.